Review of the Public Financial Management Reform Strategy for Pacific Island Countries, 2010-2020 - Allen, Richard (IMF Working Papers; Working Paper ;, 2020)
This paper reviews the Public Financial Management (PFM) reform stategy for 16 Pacific Island Countries (PICs) during the period 2010-2020. The strategy was endorsed by the finance and economic ministers of the region (FEMM) in 2010. The paper analyzes more than 30 PEFA assessments carried out across the region. The region shares the generally slow pace of PFM reform that is also a feature of most developing countries. Some PICs have improved their PFM performance significantly, while others have done less well. PFM reforms have suffered from the small size and low capacity of many PICs, poorly designed PFM roadmaps, variable political suppport for reform, and vulnerability to natural disasters. The paper recommends that in the next five years, there should be a more granular and targeted approch to PEFAs. PICs should focus on basic PFM reforms and (where capacities allow) more transparent public finances, as well as better management of climate change considerations, public infrastructure, gender inequalities, and state-owned enterprises. Perseverance by countries in implementing reforms and leadership by finance ministries are critical. PFTAC's advice is highly regarded across the region, and it could consider alternative modalities of CD delivery and stronger coordination with other development partners.